Review of Maritime Transport 2008 - Conference des Nations Unies sur le commerce et le développement (United Nations, 2009)
This annual review identifies the main developments in world maritime transport and provides world-wide statistical data. It takes a look at supply/demand equilibrium in containerized shipping, shipbuilding and shipscrapping, the development of ports, privatization and freight markets among other relevant areas. It also presents extracts of the United Nations Code of Conduct as it relates to the areas discussed.